Physicians' Desk Reference MobilePDR Review. Issue 4 (1st October 2016) - Page, Amanda
ABSTRACT: Mobile PDR is a platform and mobile application from the Physicians' Desk Reference. Specifically focusing on diagnostic care, mobile PDR houses a collection of pharmaceutical and drug information. This article will explore the functionality and usability of the mobile PDR platform including how to access, browse, and search for pharmaceutical information. It will discuss management of privacy and data.